Teaching Motion Concepts through Pokemon Unite: Students’ Acceptance and Experiences - Sanchez, Joje Mar (Schrödinger: Journal of Physics Education, 2024)
Purpose of this study: This study aims to improve student learning outcomes and engagement by investigating the integration of Pokémon Unite into Physics instruction.. Methodology: In this mixed-methods study, thirty Cebu City 12th graders were taught motion-related physics principles via Pokémon Unite. The game's acceptability and efficacy were evaluated using surveys and interviews. The data was analyzed using descriptive statistics and thematic analysis, guaranteeing truthful responses and data integrity. Main Findings: Results showed high student acceptance, bolstered by the game’s engaging gameplay and skillful use of Physics concepts. Students praised the game’s enjoyment, relevance, effectiveness, and engagement as a satisfying tool reflected in Physics teaching. Students' good experiences are further clarified through qualitative analysis, highlighting themes like immersive learning environments, collaborative problem-solving, personalized learning, enhanced motivation and interest, and real-world application of physics principles. These results highlight the potential of digital game-based learning in physics education and suggest additional studies and innovative strategies to improve student outcomes. Novelty/Originality of this study: This study showed that Pokémon Unite is a useful teaching tool for Physics and has a high student acceptance and participation level. Through digital game-based learning, it provides fresh perspectives on individualized instruction, group problem-solving, and the practical application of physics ideas.